Tracy: basecalling, alignment, assembly and deconvolution of sanger chromatogram trace files - Rausch, Tobias; Fritz, Markus Hsi-Yang; Untergasser, Andreas; Benes, Vladimir (BMC genomics, 2020)
DNA sequencing is at the core of many molecular biology laboratories. Despite its long history, there is a lack of user-friendly Sanger sequencing data analysis tools that can be run interactively as a web application or at large-scale in batch from the command-line.
Gesehen am 21.04.2020